2015
DOI: 10.14414/jebav.v18i3.510
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of behavioral intention on ABC system adoption: Model of information systems technology and success acceptance

Abstract: A B S T R A C T This study aims to examine the effect of individual behavioral change on the adoption of activity-based costing (ABC) system and its usage, using Unified Theory of Acceptance and Use of Technology (UTAUT) and A B S T R A K Penelitian ini bertujuan untuk menguji pengaruh perubahan perilaku individu pada adopsi activity-based costing system (ABC) dan penggunaannya, dengan Unified Theory of Acceptance and Use of Technology (UTAUT) dan Information System

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
3
2
Order By: Relevance
“…A surprising finding was on the relationship between perceived information content quality and intention to use e-recruitment. The insignificant relationship between information content quality and intention to use erecruitment deviated from past studies that found a positive relationship between them (Lin and Lu, 2000;Indipenrian et al, 2015). Contrary to the results of this study, the research by Indipenrian et al (2015) pointed out that social factors and information quality influences the behavioral intention of individual to adopt a system.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…A surprising finding was on the relationship between perceived information content quality and intention to use e-recruitment. The insignificant relationship between information content quality and intention to use erecruitment deviated from past studies that found a positive relationship between them (Lin and Lu, 2000;Indipenrian et al, 2015). Contrary to the results of this study, the research by Indipenrian et al (2015) pointed out that social factors and information quality influences the behavioral intention of individual to adopt a system.…”
Section: Discussioncontrasting
confidence: 99%
“…The insignificant relationship between information content quality and intention to use erecruitment deviated from past studies that found a positive relationship between them (Lin and Lu, 2000;Indipenrian et al, 2015). Contrary to the results of this study, the research by Indipenrian et al (2015) pointed out that social factors and information quality influences the behavioral intention of individual to adopt a system. A plausible explanation is that the perceived information quality on established internet recruiting sites such as Monster.com are generally good and therefore less attention is paid to the quality.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations